(untitled) (Journal of Bangladesh Academy of Sciences, 2018)
The present study evaluated the analgesic, anti-inflammatory and antioxidant activities of Alternanthera pungens kunth.The ethanolic extract of Alternanthera pungens (EAP) showed analgesic effects by exerting ameliorated reaction time 40.79% and 44.74% at a dose of 250 and 500 mg/kg,respectively, whereas standard was 41.78% by the hot plate test. Results of writhing inhibition were statistically significant (p <0.05) when compared to control. In addition to that, anti-inflammatory effects were also evaluated against denaturation of protein and the result was significant. Scavenging activity of EAP was 80.95% at the concentration of 800µg/mL. Moreover, HPLC-DAD analysis of EAP was also carried out to determine the presence of phenolic constituents & noted the presence of epicatechin,vanillin, p-coumaric acid etc. These studies inferred that EAP possesses analgesic, anti- inflammatory and antioxidant potential which might be due to presence of phytochemicals like flavonoids, tannins and phenolic compounds. Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 129-136, 2018